Towards a FPGA-controlled deep phase modulation interferometer. (April 2015) - Terán, M; Martín, V; Gesa, Ll; Mateos, I; Gibert, F; Karnesis, N; Ramos-Castro, J; Schwarze, T S; Gerberding, O; Heinzel, G; Guzmán, F; Nofrarias, M
Abstract: Deep phase modulation interferometry was proposed as a method to enhance homodyne interferometers to work over many fringes. In this scheme, a sinusoidal phase modulation is applied in one arm while the demodulation takes place as a post-processing step. In this contribution we report on the development to implement this scheme in a fiber coupled interferometer controlled by means of a FPGA, which includes a LEON3 soft-core processor. The latter acts as a CPU and executes a custom made application to communicate with a host PC. In contrast to usual FPGA-based designs, this implementation allows a real-time fine tuning of the parameters involved in the setup, from the control to the post-processing parameters.